Higher mathematics teaching design based on military problem - Xie Jun; Yuan Jinlong; Liu Weili (SHS Web of Conferences, 2023)
Integrating military cases into the teaching of higher mathematics can stimulate students’ interest in learning and lay a good foundation for students to consciously apply mathematical knowledge and methods to solve military problems they will face in the future. Therefore, this paper first expounds the significance of integrating military problems into higher mathematics, then expounds the selection principles of integrating military problems into higher mathematics, and finally combines part of the teaching content of higher mathematics with practical problems with military background, and uses the "problem solving" of military problems to design the classroom content. Demonstrate the use of mathematical methods in solving practical problems.